The Practice of Mediation Communication in Resolving Divorce Cases at the 1A Religious Court in Makassar - Muh Insan Kamil; Abdul Khalik; Nurlaelah Abbas (Jurnal Mercusuar, 2023)
of divorce dispute resolution at the 1A Religious Court in Makassar. The research adopts a qualitative descriptive approach, with a case study method conducted at the 1A Religious Court in Makassar. The data sources for this research include two judge mediators and ten litigants involved in the cases. Data collection methods used in this study include observation, interviews, and documentation. The researcher acts as the main instrument in this research. Data processing and analysis are conducted in three stages: data reduction, data presentation, and drawing conclusions. The research findings reveal that communication practices in the mediation process at the 1A Religious Court in Makassar involve interpersonal communication, which is demonstrated through verbal communication with openness, empathy, and humility, as well as nonverbal communication including body language, facial expressions, and tone of voice. The communication between the mediator and the litigants is two-way, characterized by a friendly and informal atmosphere, and the discussion mainly revolves around private matters. Additionally, the application of interpersonal communication in the mediation process at the 1A Religious Court in Makassar also employs psychological, sociological, and religious approaches. The implications of this research highlight that effective interpersonal communication can influence and positively change the litigants’ perceptions of the mediation process at the 1A Religious Court in Makassar.